Microsurgical dissection of Sylvian fissure: short technical videos of third generation cerebrovascular neurosurgeons - Muḥammad, Sajjad; Tanikawa, Rokuya; Lawton, Michael T.; Regli, Luca; Niemelä, Mika; Korja, Miikka (Acta neurochirurgica, 2019)
Multiple intracranial pathologies, including aneurysms of the middle cerebral artery, distal basilar artery, and suprasellar pathologies require the microsurgical opening of the Sylvian fissure. Delicate splitting of the arachnoid and safe microdissection of the veins, arteries, and brain parenchyma is the key to successful surgery through the Sylvian fissure corridor. We hypothesize that the geographical and historical environment in which neurosurgeons learn their operative skills is subject to a number of extrinsic influences, including cultural nuances of surgical techniques. Here we try to illustrate some cultural differences and technical aspects of the opening of the Sylvian fissure by four “third generation” cerebrovascular neurosurgeons from three different continents.